Zwei Gemälde niederländischer Meister in Zagreb – Provenienz und Rezeptionsgeschichte - Pasini Tržec, Iva (RIHA Journal, 2015)
The authors present the complex reception history of two paintings in the Dutch Painting Collection at the Strossmayer Gallery of Old Masters in Zagreb, reconstructing their provenance on the basis of archival documents and the analysis of heraldic insignia and other marks on the reverse. The circumstances of the purchase of Master of the Virgo inter Virgines' Throne of Mercyin Milan 1872 reflect the Italian art market development at the time. The provenance of the Nativity and the Adoration of the Shepherds by The Master of the Douai Carrying of the Cross, possibly Master J. Kock, purchased in Cologne 1871, includes prominent owners: family Peltzer, family Wittelsbach, Josef Höger, and Johann Friedrich Fromm. The importance of these two paintings was acknowledged by their inclusion in the famous exhibition held at Museum Boymans in Rotterdam 1936.